”I trust what’s written but I don’t think it’s good”: Old age pensioners’ persistency in the practice of obtaining information from the news media - Ljuslinder, Karin; Lundgren, Anna Sofia (MedieKultur: Journal of media and communication research, 2017)
In spite of the fact that we are living in a digital era the position of traditional news media as the first chosen source of information has not been altered. This is especially true when it comes to older persons. What are the reasons for this persistency? This article gives an account of how older persons reflect on whether and why they believe in, and trust, news press reporting and their reasons for acquiring news from traditional news media. Using a discourse theoretical logics approach we found that whether or not the informants believed in and trusted the news they all referred to an overarching fantasy stating that it is a right and an obligation of an ideal citizen to update oneself of the surrounding world via the news media. We also found social habits to be crucial for the informants’ practice of obtaining information from the news media.